Penerapan Model Pembelajaran Picture And Picture Untuk Meningkatkan Hasil Belajar Siswa Materi Bangun Datar Pelajaran Matematika Kelas I SD Alfityah Pekanbaru - Azizah Tulfauziah; Salman Salman; Sakban Sakban (Politeknik Kampar, 2024)
The low learning outcomes of students in flat shapes material in grade 1 elementary school mathematics lessons is the main problem faced. Students often have difficulty understanding the basic concepts of flat shapes taught conventionally. The aim of the research is to improve student learning outcomes by using the Picture and Picture learning model for Flat Building Material in Mathematics Lessons. This research method includes Classroom Action Research (PTK) which was carried out in two cycles. Each cycle consists of four stages, namely design, implementation, observation and reflection. The research results obtained are (1) teacher activity in cycle I using the Picture and Picture learning model from 83.92% to 92.85% in the cycle II, (2) student activities in cycle I using the Picture and Picture model 75% to 91% in cycle II and (3) learning outcomes for Flat Figure material in Mathematics lessons in cycle I using the Picture and Picture model 60% to 90% in cycle II. This shows that the student learning outcomes for Mathematics Lesson Flat Figure Material using the Picture and Picture Learning model show very positive results.